Epidermal UV-screening in vascular plants from Svalbard (Norwegian Arctic) - Nybakken, Line; Bilger, Wolfgang; Johanson, Ulf; Björn, Lars Olof; Zielke, Mathias; Solheim, Bjørn (Polar Biology, 2004)
Stratospheric ozone depletion is most pronounced at high latitudes, and the concurring increased UV-B radiation might adversely affect plants from polar areas. However, vascular plants may protect themselves against UV-B radiation by UV-absorbing compounds located in the epidermis. In this 3-year study, epidermal UV-B (lambda(max) 314 nm) and UV-A (lambda(max) 366 nm) screening was assessed using a fluorescence method in 12 vascular species growing in their natural environment at Svalbard. The potential for acclimation to increased radiation was studied with artificially increased UV-B, simulating 11% ozone depletion. Open-top chambers simulated an increase in temperature of 2-3degreesC in addition to the UV-B manipulation. Adaxial epidermal UV-B transmittance varied between 1.6 and 11.4%. Artificially increased UV-B radiation and temperature did not consistently influence the epidermal UV-B transmittance in any of the measured species, suggesting that they may not have the potential to increase their epidermal screening, or that the screening is already high enough at the applied UV-B level. We propose that environmental factors other than UV-B radiation may influence epidermal UV-B screening.